The Concept of Calligraphy Learning at the Pesantren for the Fine Arts and Calligraphy of the Qur'an (PSKQ) Modern Kudus - Rika Ananda Yunisa (Jurnal Recoms, 2024)
Calligraphy is one of the Islamic arts that has received great attention from Muslims. Calligraphy as an Islamic art is the most important aspect of Islamic science, the Arabic Qur'an is an obligation to study Arabic grammar. One of the skills in Arabic grammar, namely Maharah Kitabah, calligraphy is to improve Arabic grammar according to the rules, both in terms of length, short in the number of latters to be stylish and beautiful. Modern Kudus Islamic Arts and Calligraphy Islamic Boarding School (PSKQ) provides a platform for studying the art of calligraphy in a systematic, effective and efficient manner. The intent and purpose of this research is to find out the learning system that exists in the modern PSKQ holy boarding school. From the results of the literature review, it was found that the art of calligraphy plays an important role in writing skills that can be expressed through writing and improve the grammar of the appropriate rules as beauty in writing. Methods of teaching the rules include tracing, imitating and modifying them using the Syauqi and Izzat styles.